Study on adsorption parameter to remove zinc from spent ipa using activated carbon - HaniShazwani, Mohd Suhaimi (2012)
Heavy metal is potential hazard to the environment and cause damage to ecosystems and human health. The Printed Circuit Boards (PCB) contains heavy metal; Zinc was treated by Isopropyl Alcohol (IPA) for washing process. IPA is used widely as a solvent and as a cleaning fluid. However large amount of washed IPA would be produced during operation and this should be treated effectively by proper method. It also requires high cost to treat solvent waste that contains hazardous heavy metal. Moreover the use of adsorbent is necessary to be recovered for reducing the washing operation cost. The adsorption process is used to remove Zinc from spent of IPA using Activated Carbon (AC) as adsorbent. The sample is being characterize before mixing with Activated Carbon and conducted in a shaking incubator for adsorption process. The solution then undergo centrifugation and filtration before analyze using Atomic Absorption Spectroscopy (AAS). The optimum adsorption of Activated Carbon dosage, agitation time and pH are being investigated. The high values of Activated Carbon dosage will increase the surface area with more adsorption site, the more adsorption process occur until reach concentrated limit due to overlapping of adsorption site as result of overcrowding of adsorbent particles. The agitation time is also directly proportional to the adsorption process. On the other hand, removal of Zinc without agitation time was found to be appropriate for maximum adsorption because all the adsorbents surface and quantities are having optimum contact capability with adsorbate (Zinc). The pH value will affect the degree of ionization of a species whereby in this experiment, pH 8 was observed to be the most suitable for adsorption process to occur. In term of isotherms compatibility, adsorption of Zn onto Activated Carbon satisfied the both Langmuir and Freundlich isotherms. As the conclusion, the process is significant to reduce the operating cost of adsorbent reuse and factory’s waste disposal cost through waste minimization and health hazard contribute from the heavy metal contaminant. It is alternative way to remove the heavy metal in industrial effluent electronic organic waste discharge.